2008
DOI: 10.1530/eje-07-0815
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin versus repaglinide on non-glycaemic cardiovascular risk markers related to inflammation and endothelial dysfunction in non-obese patients with type 2 diabetes

Abstract: Objective: In patients with type 2 diabetes mellitus (T2DM), biomarkers reflecting inflammation and endothelial dysfunction have been linked to cardiovascular disease (CVD biomarkers) and metabolic regulation. In T2DM patients, metformin and insulin secretagogues have demonstrated equal antihyperglycaemic potency. Here, we report the effect of metformin versus an insulin secretagogue, repaglinide, on CVD biomarkers in non-obese T2DM patients. Design and methods: Single-centre, double-masked, double-dummy, cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 74 publications
6
54
0
4
Order By: Relevance
“…It has previously been reported that metformin treatment improves endothelial function (13), and our findings are in agreement with one other human study, where metformin, in contrast to treatment with repaglinide, improved markers of endothelial function, such as von Willebrand factor, tissue plasminogen activator, plasminogen activator inhibitor-1, and intercellular adhesion molecule despite similar effects on the glycemic levels (16). Metformin has also been reported to improve endothelial function in normoinsulinemic, normalweight polycystic ovary syndrome patients (35), suggesting a possible direct effect of the drug on arterial cells beside putative secondary effects due to the glucose-lowering properties.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has previously been reported that metformin treatment improves endothelial function (13), and our findings are in agreement with one other human study, where metformin, in contrast to treatment with repaglinide, improved markers of endothelial function, such as von Willebrand factor, tissue plasminogen activator, plasminogen activator inhibitor-1, and intercellular adhesion molecule despite similar effects on the glycemic levels (16). Metformin has also been reported to improve endothelial function in normoinsulinemic, normalweight polycystic ovary syndrome patients (35), suggesting a possible direct effect of the drug on arterial cells beside putative secondary effects due to the glucose-lowering properties.…”
Section: Discussionsupporting
confidence: 93%
“…These explanations are mainly based on data from experimental animal and in vitro studies. A few results from human studies have, however, indicated that there is an effect of metformin treatment on endothelial markers and this effect may be independent of the effects on the glycemic status (16).…”
mentioning
confidence: 99%
“…15,27 Furthermore, PAI-1 levels repeatedly have been reported to be markedly lower in patients with diabetes that are treated with metformin. 28,29 In addition, results of in-vitro studies and studies in TNF receptor 1 (TNFR1)À/À mice suggest that PAI-1 is induced through TNFa receptor 1-dependent signalling cascades in the liver. 15,30 It further has been shown in in-vitro studies that metformin can block the TNFadependent induction of PAI-1 through yet not fully understood mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a high risk of developing CD, such as diabetic patients, it is important to improve endothelial function since vascular damage may continue even when good glycemic control has been achieved (Volpe et al, 2007). Accordingly, some therapeutic strategies have been directed towards the stimulation of distinct processes that may reestablish the function of the endothelium, including the use of 3-hydroxy-3-methylglutaryl www.intechopen.com coenzyme A reductase inhibitors (Endemann & Schiffrin, 2004), the angiotensin converting enzyme (ACE) inhibitors , selective blockade of the AT1 receptor of angiotensin-II (ARBs) (Behrendt & Ganz, 2002) and folic acid supplementation , antioxidants , antidiabetics (Lund et al, 2008), insulin and others (Grover-Páez et al, 2007). All these strategies are aimed at decreasing the progress of atherosclerotic disease Herein, we review the literature about endothelial dysfunction in diabetes mellitus with regards to its pathogenesis at molecular and clinical level, and possible available mode of therapy.…”
Section: Introductionmentioning
confidence: 99%